2017
DOI: 10.1007/s11356-017-0581-2
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian growth impairment after chronic exposure to Roundup Ultramax® in the estuarine crab Neohelice granulata

Abstract: Adult females of the estuarine crab Neohelice granulata were exposed to the glyphosate formulation Roundup Ultramax® during the entire 3-month pre-reproductive period. At the end of the assay, a significant higher increment of glycemia was noted at both glyphosate concentrations assayed (0.01 and 0.2 mg/L, acid equivalent). Although no differences were observed in the gonadosomatic index, a significantly higher proportion of reabsorbed vitellogenic oocyte was observed at the highest glyphosate concentration, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
0
6
0
4
Order By: Relevance
“…Toxicity to the water flea (Daphnia magna) is of special importance, and not only formulated glyphosate-based herbicides (Cuhra et al, 2013;Ørsted and Roslev, 2015), but also glyphosate residues in GT soybean were shown to exert toxicity on this standard ecotoxicity indicator organism. Effects of glyphosate on somatic and ovarian growth, as well as of glyphosatebased formulations on ovarian growth and immune status of freshwater and estuarine crab species were reported (Hong et al, 2017;Avigliano et al, 2018;Canosa et al, 2018). Toxicities have extensively been reported for fish, including the zebrafish D. rerio, on which both glyphosate (Armiliato et al, 2014;Lopes et al, 2014;Uren Webster et al, 2014) and its formulated products (Bridi et al, 2017;Sulukan et al, 2017) were found to exert acute toxicity through inhibited carbonic anhydrase activity due to oxidative stress (production of reactive oxygen species), cellular apoptosis, effects on locomotor activity and aversive behavior, as well as reproduction disorders, deteriorating sperm quality, embryotoxicity malformations, and other endocrine disruption symptoms.…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%
“…Toxicity to the water flea (Daphnia magna) is of special importance, and not only formulated glyphosate-based herbicides (Cuhra et al, 2013;Ørsted and Roslev, 2015), but also glyphosate residues in GT soybean were shown to exert toxicity on this standard ecotoxicity indicator organism. Effects of glyphosate on somatic and ovarian growth, as well as of glyphosatebased formulations on ovarian growth and immune status of freshwater and estuarine crab species were reported (Hong et al, 2017;Avigliano et al, 2018;Canosa et al, 2018). Toxicities have extensively been reported for fish, including the zebrafish D. rerio, on which both glyphosate (Armiliato et al, 2014;Lopes et al, 2014;Uren Webster et al, 2014) and its formulated products (Bridi et al, 2017;Sulukan et al, 2017) were found to exert acute toxicity through inhibited carbonic anhydrase activity due to oxidative stress (production of reactive oxygen species), cellular apoptosis, effects on locomotor activity and aversive behavior, as well as reproduction disorders, deteriorating sperm quality, embryotoxicity malformations, and other endocrine disruption symptoms.…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%
“…A first in vivo assay carried out with technical glyphosate during the entire pre-reproductive period (3 months), showed a significant incidence of oocyte reabsorption, but just at the highest glyphosate concentration tested [~ 35% in 1 mg/L concentration, Figure 2 in ( 22 ), Figure 1A here]. A further in vivo assay, made during the same period with the commercial glyphosate formulation Roundup Ultramax ® , also showed a significant incidence of oocyte reabsorption in the ovary, together with decreased vitellogenic protein content by gram of ovary; these results were found in females exposed to 0.2 mg/L of glyphosate presented as the active ingredient in the commercial formulation above mentioned [Figures 2 and 3 in ( 23 ), Figure 1B here]. Based on the results of these long-term assays, contributive toxicity of the coadjuvants presented in the commercial formulation seems to have been occurred.…”
Section: In Vivo Effects On Female Crabsmentioning
confidence: 70%
“…Adapted from Canosa et al. ( 23 ). (C) Assay made with both technical and formulated (Roundup Ultramax ® ) glyphosate, during 32 days, in post-hatching females.…”
Section: In Vivo Effects On Female Crabsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although only few studies have been carried out on mollusks, it has been demonstrated that the herbicide is particularly active on the juvenile phases of C. gigas, a species in which the gonadal indices were altered after exposure to commercial formulations (Séguin et al 2017). Nevertheless, GBH affected the ovarian growth and reduced the amount of VTG in the oocytes of the crab Neohelice granulata (Canosa et al 2018).…”
Section: Discussionmentioning
confidence: 99%